Connecting knowledge for text construction through the use of graphic organizers - Reyes, Elsy Camila (Colombian Applied Linguistics Journal, 2011)
This study analyzed how basic level students comprehend short descriptive texts and rewrite their texts through the use of graphic organizers (GOs). The research was built upon the qualitative research paradigm with the inclusion of descriptive and introspective approaches. The study was carried out at a prestigious private school in Bogotá, Colombia, with basic English level II sixth graders. Data was gathered through focus groups, GOs, and students’ documents. The results of the study demonstrated that students made connections with previous knowledge acquired at school as part of the curriculum or at home as part of their daily experiences. Participants organized the information in principal and supporting ideas in order to comprehend and rewrite their texts. According to the results, the study found that learners have previous ideas or knowledge that let them complement, organize, or re-direct a given topic.